Interaction between cigarettes and propranolol in treatment of angina pectoris. Issue 6234 (19th July 1980) - Fox, K; Jonathan, A; Williams, H; Selwyn, A
Abstract : To determine whether cigarette smoking interferes with the medical management of angina pectoris, 10 patients with angina pectoris who smoked at least 10 cigarettes a day were studied before, during, and after a standardised maximal exercise test. This was done at the end of four randomly allocated one-week treatment periods during which the patients took glyceryl trinitrate while not smoking, took glyceryl trinitrate while smoking, took glycerly trinitrate and propranolol (380 mg/day) while not smoking, and took glyceryl trinitrate and propranolol while smoking. Carboxyhaemoglobin was measured to ensure compliance. Smoking was associated with a significantly higher heart rate, blood pressure, number of positions with ST-segment depression, and total ST-segment depression after exercise than non-smoking (p < 0.01) whether or not the patients were taking propranolol. These results suggest that smoking aggravates the simple haemodynamic variables used to assess myocardial oxygen requirements and the exercise-induced precordial electrocardiographic signs of myocardial ischaemia. These effects were still evident after treatment with propranolol and represent a hindrance to the effective medical treatment of angina pectoris.